2023
DOI: 10.3390/molecules28104059
|View full text |Cite
|
Sign up to set email alerts
|

Novel Approach to the Construction of Fused Indolizine Scaffolds: Synthesis of Rosettacin and the Aromathecin Family of Compounds

Shohta Mizuno,
Takashi Nishiyama,
Mai Endo
et al.

Abstract: Camptothecin-like compounds are actively employed as anticancer drugs in clinical treatments. The aromathecin family of compounds, which contains the same indazolidine core structure as the camptothecin family of compounds, is also expected to display promising anticancer activity. Therefore, the development of a suitable and scalable synthetic method of aromathecin synthesis is of great research interest. In this study, we report the development of a new synthetic approach for constructing the pentacyclic sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
(86 reference statements)
0
4
0
Order By: Relevance
“…The mechanism of the generation of compound 12b from substrate 12a was proposed by the authors (Scheme 21). The addition of NHC to substrate 12a yields In 2023, Choshi et al reported a new method for the synthesis of rosettacin by using thermal cyclization and a Reissert-Henze-type reaction as the key step [41] (Scheme 22). Here, 2-Chloroquinoline-3-carbaldehyde 8a reacted with NaI and concentrated HCl to yield 2-iodoquinoline 13a.…”
Section: Synthesis Of Rosettacinmentioning
confidence: 99%
“…The mechanism of the generation of compound 12b from substrate 12a was proposed by the authors (Scheme 21). The addition of NHC to substrate 12a yields In 2023, Choshi et al reported a new method for the synthesis of rosettacin by using thermal cyclization and a Reissert-Henze-type reaction as the key step [41] (Scheme 22). Here, 2-Chloroquinoline-3-carbaldehyde 8a reacted with NaI and concentrated HCl to yield 2-iodoquinoline 13a.…”
Section: Synthesis Of Rosettacinmentioning
confidence: 99%
“…Initially, hydroxypyridone (38) was treated using Tf 2 O in pyridine to obtain a triflate (39) with an 89% yield, followed by the Heck reaction of 39 with methyl 2,4-pentadienoate (40) in the presence of PdCl 2 (PPh 3 ) 2 and Et 3 N to obtain an alkene (41) with a 64% yield (Scheme 5). Next, 41 was subjected to FVP cyclization to obtain pyrroloisoquinolin-5one (42) with a 77% yield; to introduce a carbonyl group to the 1-position, a ketone (43) with a 75% yield was obtained through SeO 2 and Dess-Martin periodinane (DMP) oxidations.…”
Section: Categorymentioning
confidence: 99%
“…(Figure 1). [2] In recent times, transition‐metal‐catalyzed functionalization of less reactive C−H bonds has become significant. Also C−C and C−X (X=heteroatom) bond formation through direct C−H bond transformation becomes significant.…”
Section: Introductionmentioning
confidence: 99%